IDEA OF ELECTRICAL TOMOGRAPHY SYSTEM FOR MONITORING LUNG VENTILATION - Rymarczyk, Tomasz; Adamkiewicz, Przemysław; Tchórzewski, Paweł (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
In many applications of electrical tomography, such as monitoring the lungs of unconscious intensive care patients, data acquisition on the entire boundary of the body is impractical. The boundary area available for electrical tomography measurements is restricted. Physiological processes that produce changes in the electrical conductivity of the body can be monitored by hybrid algorithms. This paper presents the architecture of the system based on electrical tomography.